Phytochemical Screening and In-Silico Investigation of 2-Benzoxazolinone from Acanthus Ilicifolius Linn. as Dual Inhibitors of Cyclooxygenase-2 and 5-Lipooxygenase Enzymes - AR Saranya; S Manikandan; T Ramanathan; KS Kesavanarayanan; LK Teh; MZ Salleh (International Journal of Phytomedicine, 2014)
2-Benzoxazolinone (BOA) is a phytoconstituent of a mangrove plant Acanthus ilicifolius Linn used to treat inflammatory diseases. Anti-inflammatory agents with dual inhibiting properties of COX-2/5-LOX enzymes activities are said to possess anti-inflammatory effect and are devoid from side effects but not yet available on the market. Therefore, the dual inhibiting property of BOA and its derivatives [6-Bromo-BOA (6-BrBOA), 6-Chloro-BOA (6-ClBOA), Hydroxy-BOA (HBOA) and 6-methoxy BOA (6-MBOA)] is worth investigating. Initially, BOA content in supercritical CO2 fluid extract (SCFE) of A.ilicifolius leaves was estimated using ultra high performance liquid chromatography (UHPLC). Later, genetic algorithm based GOLD docking simulation was employed to dock BOA and its derivatives into the binding pocket of COX-2 and allosteric binding site of 5-LOX. Probable hit ligand was ranked using an evaluation criterion based on the GOLD docking score and the ligand binding mode. The UHPLC chromatogram revealed the presence of BOA in SCFE. High gold docking scores ranging from 40.89 to 43.13 were observed in all the tested ligands with COX-2 and three ligands namely; 6-BrBOA (42.67), 6-ClBOA (41.79) and BOA (38.90) showed high docking scores with 5-LOX allosteric binding site. In conclusion, UHPLC method could be used for the determination of BOA content in A.ilicifolius. BOA and its analogues could be a promising lead for developing dual inhibitors of COX-2/5-LOX enzymes as verified by computational studies.